Emancipatory Thought in Reflecting on Islamic Theology - Saila Salsabila; Mulyana Mulyana; Kifah Gibraltar Bey Fananie (Gunung Djati Conference Series, 2022)
The purpose of this study is to discuss emancipatory thinking in Islamic theology. This research method uses a qualitative type through literature study with content analysis. The results of this discussion include reasoning in traditional theological ideas, emancipatory ideas in Islam, and emancipatory paradigms for Islamic social theology. This study concludes that emancipation is basically inseparable from the theory of critical reading that has developed in the contemporary era which is associated with critical interpretation of religion. In this regard, an emancipatory divine reasoning is needed, but not fixated on defending God, but more importantly building a commitment to solving various problems of human life and social realities.